A Comprehensive Review of a Decade of Field PV Soiling Assessment in QEERI’s Outdoor Test Facility in Qatar: Learned Lessons and Recommendations - Brahim Aïssa (14157243) (2023)
Soiling of photovoltaic (PV) modules is a major issue due to its critical impact on PV performance and reliability, especially in the desert and arid regions such as the state of Qatar. Soiling frequently results in a severe reduction in PV power generation, which drastically affects the economical profitability of the PV plant, and therefore, must be mitigated. The most common way of mitigating PV soiling is surface cleaning. However, the latter could consequently increase the associated operation and maintenance (O&M) cost of the PV site. However, previous studies indicated that even if the best-optimized cleaning schemes are used, the actual global solar-power production can still be reduced by about 4%, which is associated with at least EUR 5 billion in annual revenue losses worldwide. This loss is expected to reach a conservative value of EUR 7 billion in 2023. Accordingly, investigating the interplayed physics phenomena related to the various soiling processes, the site-specific O&M costs, along with a techno-economical assessment of state-of-the-art soiling mitigation strategies (including innovative anti-soiling coating materials) is of paramount importance. The goal of this comprehensive report is to provide the solar community at large, and those focusing on the desert environment in particular, with real field measurements that provide key findings and challenges in addressing soiling research obtained from multiyear testing at the Outdoor Test Facility (OTF) field station, located in the desert environment of the city of Doha, in the state of Qatar. Other Information Published in: Energies License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/en16135224